Exploring Officer Arrest Discretion Following State Policy Changes in Intimate Partner Violence - Mason, Philip B. (Violence against women, 2021)
In 2015, South Carolina passed the Domestic Violence Reform Act giving officers increased arrest discretion and rescinding mandatory arrest laws for intimate partner violence (IPV). Analyses using incident reports (2016/2017) from South Carolina show that officers primarily rely on the presence of five variables to determine arrest: children, injury, property destruction, offender at scene, and weapons. Cases with Black female victims are more likely to result in arrest, suggesting that Black males are being criminalized. We conclude that officers are reluctant to use individual discretion and rely on a form of structured discretion provided by administrators that shapes local culture and decision-making.